PELATIHAN PEMBUATAN PUPUK BOKASHI PADA KELOMPOK TANI DI KECAMATAN OBA KOTA TIDORE KEPULAUAN - Yunus Syafie; Nurdianawaty Djumadil (JURNAL PENGABDIAN MANDIRI, 2022)
The agricultural sector has an important role in the development of the Indonesian economy, thus making the government pay great attention to the agricultural sector to its sub-sectors. One of the concerns is the use of fertilizers to increase crop productivity. Most farmers use chemical fertilizers for their crops. Excessive use of chemical fertilizers will eventually disrupt the balance of the ecosystem and in a long time the soil will become barren. Oba sub-district is one of the sub-districts in the Tidore Islands City located on the mainland of the island of Halmahera, which is known as an agricultural area that has the potential for agricultural products, especially secondary crops and horticulture. Farmers have started to complain that crop production has decreased and the ecological effects caused by the use of chemical fertilizers, namely rats, have increased in population compared to previous years. This is because the use of chemical fertilizers destroys soil fertility due to a lack of a much needed macro nutrient, namely nitrogen. Community service activities are carried out aiming to train and improve the skills of farmer groups in Oba District, Tidore Islands City in making bokashi fertilizer. The implementation of this PKM activity uses a socialization and training approach and its application starts from the preparation of materials to the processing into bokhasi fertilizer products. Service activities received a very good response from farmer groups and were very supportive of the program being implemented. Farmer group members can make bokashi and have used it in their garden